Enacting criminal futures: data practices and crime prevention - Leese, Matthias (Policing and society, 2023)
This paper analyzes how in predictive policing, data ‘make’ criminal futures that can be subjected to crime prevention. In doing so, it shows that the production of specific accounts of the future is predicated on the data practices of police departments. Specifically, the analysis identifies two sets of data practices that play a key role in how predictive policing brings specific criminal futures into being and renders them amenable to crime prevention measures. The first one pertains to the production of crime data and draws attention to the digital devices and interfaces that co-constitute how criminal phenomena are recorded and classified. The second one relates to ‘quality control’, i.e. the corrections and updates that keep on transforming crime data even after their original production. Theoretically, the analysis builds on Law and Urry’s concept of ‘enactment’ and substantiates how data-driven analytics perform fluid versions of social realities and simultaneously subject them to interventions. The conceptual lens of enactment allows us to understand how seemingly mundane activities such as producing reports from crime scenes and amending case files throughout an investigation are performative in the sense that they contribute to the making of crime forecasts and corresponding prevention measures. The criminal futures that the police target in an effort to render crime prevention more effective and efficient should thus be understood as contingent on the everyday practices of field officers and analysts.